Isoflurane anesthesia elicits protein pattern changes in rat hippocampus - Kalenka, Armin; Groß, Benjamin; Maurer, Martin H.; Thierse, Hermann-Josef; Feldmann, Robert Enrico (Journal of neurosurgical anesthesiology, 2010)
Postoperative cognitive dysfunction (POCD) is a known phenomenon occurring after anesthesia with volatile anesthetics (VA), such as isoflurane. Recent reports suggest that VA interact with neurodegenerative disease-associated proteins including compounds with pathogenic relevance in Alzheimer disease (AD) and induce processes that may be linked to AD neuropathology. Unfortunately, our present understanding of the exact anesthetics' molecular mechanisms of action, their side effects on the brain, and their catenation with AD pathology is still limited. The present study analyzes the differential proteome of the hippocampus immediately after and 3 days after a 3-hour 1 minimal alveolar concentration isoflurane anesthesia in rats.